KEPUTUSAN PEMBELIAN DITINJAU DARI CITRA MEREK, GAYA HIDUP, DAN KERAGAMAN PRODUK MEREK HANASUI DI SUKOHARJO - Alifia Dhea Nur Insani; Sudarwati Sudarwati; Fithri Setya Marwati (ITB AAS Indonesia Surakarta, 2023)
This research aimed to evaluate how factors like as brand image, lifestyle, and product diversity influence consumers’ decision to purchase Hanasui cosmetic in Sukoharjo. A quantitative strategy has been used in its research. The population used 636 customers of one of the agents in Sukoharjo, and the sampel size is set at 100 customers thanks to a non-probability, purposive sampling technique. In Sukoharjo, the variables of brand image, lifestyle, and product diversity all had a positive influence in purchase decision of Hanasui brand cosmetic items, and this influence is statistically significant as well. The modified R-Square value showed that 70,4%, which suggest that factors such as brand image, lifestyle, and product diversity play a role in the decision of whether or not to purchase Hanasui product in Sukoharjo. Another factors that are not include in this study was influenced 29,6%. Keywords : Brand Image, Lifestyle, Product Diversity, Purchasing Decisions